The Cumulus Cell Layer Protects the Bovine Maturing Oocyte Against Fatty Acid-Induced Lipotoxicity. Issue 1 (1st January 2015) - Lolicato, Francesca; Brouwers, Jos F.; de Lest, Chris H.A. van; Wubbolts, Richard; Aardema, Hilde; Priore, Paola; Roelen, Bernard A.J.; Helms, J. Bernd; Gadella, Bart M.
Abstract: Mobilization of fatty acids from adipose tissue during metabolic stress increases the amount of free fatty acids in blood and follicular fluid and is associated with impaired female fertility. In a previous report, we described the effects of the three predominant fatty acids in follicular fluid (saturated palmitate and stearate and unsaturated oleate) on oocyte maturation and quality. In the current study, the effects of elevated fatty acid levels on cumulus cells were investigated. In a dose-dependent manner, the three fatty acids induced lipid storage in cumulus cells accompanied by an enhanced immune labeling of perilipin-2, a marker for lipid droplets. Lipidomic analysis confirmed incorporation of the administered fatty acids into triglyceride, resulting in a 3- to 6-fold increase of triglyceride content. In addition, palmitate selectively induced ceramide formation, which has been implicated in apoptosis. Indeed, of the three fatty acids tested, palmitate induced reactive oxygen species formation, caspase 3 activation, and mitochondria deterioration, leading to degeneration of the cumulus cell layers. This effect could be mimicked by addition of the ceramide-C2 analog and could be inhibited by the ceramide synthase inhibitor fumonisin-B1. Interfering with the intactness of the cumulus cell layers, either by mechanical force or by palmitate treatment, resulted in enhanced uptake of lipids in the oocyte and increased radical formation. Our results show that cumulus cells act as a barrier, protecting oocytes from in vitro induced lipotoxic effects. We suggest that this protective function of the cumulus cell layers is important for the developmental competence of the oocyte. The relevance of our findings for assisted reproduction technologies is discussed.